Barriers to application of weather and climate information in cut flower production in Benguet - Sonny N. Domingo; Adrian D. Agbon; Ma. Divina Olaguera; Anna Jennifer L. Umlas; Katrina Mae C. Zuluaga; Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 2020)
The province of Benguet holds a competitive advantage in the production of cut flowers because of its unique weather and climate; however, the access to and use of information on weather and climate phenomena in agricultural decision making is not guaranteed despite its provision. This presents a critical issue to examine given that the changing climate situation in the region could adversely affect production and living standards without reliable sources of information for the same. In this paper, the researchers thus aimed to explore the barriers in the applications of weather and climate information to cut flower production in Atok, Benguet. It was found that while barriers also exist on the side of hydrometeorological information producers' dissemination of information, there also exist significant financial, infrastructural and capacity barriers that include lack of working capital to implement optimal decision alternatives dictated by adverse weather conditions, the lack of reliable phone service and power to disseminate and access the information, and the absence of forecasts translated into the vernacular or laymanized.
Keywords: 330; Cut flower production; weather and climate information; agriculture; smallholder farming